Testing the Stability of NASICON Solid Electrolyte in Seawater Batteries - Mihaela Iordache; Anisoara Oubraham; Simona Borta; George Ungureanu; Adriana Marinoiu (Energies)
Rechargeable batteries play a crucial role in the utilization of renewable energy sources. Energy storage systems (ESSs) are designed to store renewable energy efficiently for immediate use. The market for energy storage systems heavily relies on lithium-ion batteries due to their high energy density, capacity, and competitiveness. However, the increasing cost and limited availability of lithium make long-term use challenging. As an alternative to Li-ion batteries, rechargeable seawater batteries are gaining attention due to their abundant and complementary sodium ion active materials. This study focuses on the preparation and characterization of Na3.0Zr2Si2PO12- and Na3.15Zr2Si2PO12-type ceramic membranes and testing their stability in seawater batteries used as solid electrolyte. From the surface analysis, it was observed that the Na3.15Zr2Si2PO12 powder showed a specific surface area of 2.94 m2/g compared to 2.69 m2/g for the Na3.0Zr2Si2PO12 powder. The measured NASICON samples achieved ionic conductivities between 7.42 × 10−5 and 4.4 × 10−4 S/cm compared to the NASICON commercial membrane with an ionic conductivity of 3.9 × 10−4 S/cm. Battery testing involved charging/discharging at various constant current values (0.6–2.0 mA), using Pt/C as the catalyst and seawater as the catholyte.